Lifestyle Pathways: How Family, Peers, and Social Media Shape Adolescent Consumer Behavior - Ela Wulandari; Sugeng Hadi Utomo; Lisa Rokhmani (Economics Education Department Universitas Negeri Semarang, 2025)
This study investigates the predictive relationships between social and psychological factors, namely, family economic education, peer conformity, social media, and adolescent consumer behavior, with lifestyle as a mediating variable. Employing a quantitative research design, data were collected from 400 adolescents in Semarang City, Indonesia. The analysis was conducted using PLS-SEM, which is suitable for prediction-oriented models and mediation testing. The results indicate that social media exerts the most decisive influence on adolescents’ lifestyle, significantly affecting consumer behavior. Lifestyle was confirmed as a key mediator, transmitting the influence of all three predictors to actual consumption behavior. Family economic education emerged as the most influential factor in directly shaping rational and responsible consumption behavior, whereas social media was the dominant force in shaping lifestyle patterns. These findings highlight the dual role of socialization agents: media as a digital lifestyle influencer, and the family as a foundational source of economic values and decision-making skills. The study suggests that educational institutions, families, and communities should collaborate to promote financial literacy and responsible lifestyle choices through social media platforms. Moreover, integrating educational influencers should strategically guide youth toward sustainable and informed consumption behaviors.